Technologiczne wspomaganie uczenia się matematyki - Przybyła, Tomasz (Studia Edukacyjne, 2021)
The use of Information and Communication Technology (ICT) in education during a pandemic has become a fact and a must. Before COVID-19 (for decades), the need to use ICT in education was po[1]stulated and suggested. Research carried out in this area resulted from the need to understand what technologies are potentially available for use in education, including the teaching and learning of mathematics. One important issue still to be resolved is whether and how to support children in their mathematical education using technology. This publication, referring to selected recent studies con[1]ducted worldwide, gives examples and arguments for technological support of mathematics learning.